Pengaruh Pemberian Kompos dan Pupuk Hayati terhadap Aktivitas Fosfatase dan Urease pada Tanah yang Ditanami Brokoli (Brassica oleracea L.) - Rahmansyah, Maman; Antonius, Sarjiya (Perhimpunan Biologi Indonesia, 2015)
Organic farming basically work on improving organic soil substrate which give impact to plant growth promoting bacteria. On the other hand, the use of agrochemicals leave chemical residues in the soil. In an effort to get the quality of organic matter and selected microbes as a biofertilizer material, this research had been done. Half ripe composting (HRC) process of organic substrate was utilized to enrich soil containing agrochemical residue, while ripe compost (RC) substance amended to soil free residue. That compost was used in broccoli cultivation. Microbial degrading pesticide was added to compost as biofertilizer formula. Even though plant biomass and the yield of flower was unclearly affected, but moreover the HRC application as due to Ã¢â¬Åsemi-on-site-compostingÃ¢â¬Â practices in soil containing agrochemical residue would cut off compost processing time. Soil microbial activity measured through soil respiration, urease and phosphomonoesterase indicated that the value was lower in samples collected from the soil free residue compared with soils containing residues. Utilization of chicken manure resulted in the availability of high nitrogen compounds and causing imbalance absorption by plants, compared with the use of HRC and RC in this study.ÃÂ Keywords: soil respiration, phosphatase, urease, Brassica oleracea L.ÃÂ